1973
DOI: 10.1161/01.res.32.3.385
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Calcium on Force-Velocity-Length Relations of Heart Muscle of the Cat

Abstract: The influence of calcium concentration in the bathing solution on the force-velocity relations of the isolated, electrically excited cat papillary muscle was examined. Shortening velocity was directly measured at minimum loads by unloading or load clamping the muscle from the preload (at the length, Lmax, where maximum active tension was developed) to 0 (zero-load clamp), 2, 5, 10, and 15% of the total tension, P o . All measurements were made in the physiological length range between Lmax and 12.5% below Lmax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
34
0

Year Published

1974
1974
2000
2000

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 28 publications
4
34
0
Order By: Relevance
“…After the elastic damping of the force-lengthvelocity lever feedback system was adjusted to compensate for electromechanical transients, the maximum velocity of unloaded muscle shortening (Vm.,) was obtained by abruptly decreasing the load on the muscle at the time of activation (zero load clamp). 33 The output of the amplifier of the Gould 2400 s recorder was connected to an electronic differentiator, and both of these were fed into an analog-to-digital converter (model DT 2821-F-801, Data Translation Inc., Marlborough, Mass. ), which in turn was connected to a microcomputer (model 286, COMPAQ Computer Corp., Houston, Tex.).…”
mentioning
confidence: 99%
“…After the elastic damping of the force-lengthvelocity lever feedback system was adjusted to compensate for electromechanical transients, the maximum velocity of unloaded muscle shortening (Vm.,) was obtained by abruptly decreasing the load on the muscle at the time of activation (zero load clamp). 33 The output of the amplifier of the Gould 2400 s recorder was connected to an electronic differentiator, and both of these were fed into an analog-to-digital converter (model DT 2821-F-801, Data Translation Inc., Marlborough, Mass. ), which in turn was connected to a microcomputer (model 286, COMPAQ Computer Corp., Houston, Tex.).…”
mentioning
confidence: 99%
“…18,22,23 In those experiments, activation was varied in one of several ways, including inotropic agents such as ␤-agonists, increased [Ca 2ϩ ] o , or measuring loaded shortening at various times during twitch contractions. Despite the consistent finding of Ca 2ϩ -induced alterations in power output, the subcellular factors that limit loaded shortening and relative power output in cardiac muscle remained uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Brustsaert et al (1973) have reported an increase in V'max following an increase in Ca++ concentration in the bathing medium and suggested that changes in Ca++ concentration influence the rate of turnover of cross-bridge formation between actin and myosin. The present study indicates that thiamylal and halothane may depress the Ca-regulated turnover rate of cross-bridge formation, but the depression of turnover rate by halothane is not completely counteracted by increasing Ca++ concentration.…”
Section: Discussionmentioning
confidence: 99%